Modified polytetrafluoroethylene and stretched body
By adjusting the polymerization of PTFE with hexafluoropropylene, the modified PTFE achieves high breaking strength and low extrusion pressure, addressing moldability and thermal stability issues, suitable for stretchable applications.
Patent Information
- Application Number
- JP2024202476
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-06
AI Technical Summary
Existing polytetrafluoroethylene (PTFE) materials face challenges in achieving high breaking strength while maintaining low extrusion pressure and moldability, leading to issues with paste extrudate hardness and reduced moldability.
The incorporation of hexafluoropropylene (HFP) units in specific proportions during polymerization, along with tetrafluoroethylene (TFE), results in modified PTFE with breaking strengths of 20.0N or more and extrusion pressures of 20.0 MPa or less, achieving a strength ratio of 1.80 N/MPa or higher, and improved thermal stability and moldability.
The modified PTFE exhibits high breaking strength, low extrusion pressure, and excellent moldability, with a strength ratio of 1.80 N/MPa or higher, and improved thermal stability, making it suitable for stretchable applications.
Smart Images

Figure 2025019143000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to modified polytetrafluoroethylene and an expanded body thereof. [Background technology]
[0002] When polytetrafluoroethylene is molded and highly stretched in an unsintered state, a porous polytetrafluoroethylene film is obtained. This porous film allows gases such as water vapor to pass through, but does not allow water droplets to pass through due to the strong water repellency of polytetrafluoroethylene. Taking advantage of this unique property, it is used in clothing, separation membranes, etc.
[0003] Patent Document 1 describes a polytetrafluoroethylene fine powder having units based on a comonomer such as CH2=CH-(CF2)4F.
[0004] Patent Document 2 describes a modified polytetrafluoroethylene fine powder having units based on perfluoro(methyl vinyl ether).
[0005] Patent Document 3 describes a powder of tetrafluoroethylene homopolymer or polytetrafluoroethylene having units based on hexafluoropropylene. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2011 / 055824 [Patent Document 2] JP 2015-127411 A [Patent Document 3] International Publication No. 2020 / 022355 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present disclosure is to provide a modified polytetrafluoroethylene that has high breaking strength but requires low extrusion pressure, and an expanded body using the same. [Means for solving the problem]
[0008] The present disclosure (1) is a modified polytetrafluoroethylene that contains tetrafluoroethylene units and hexafluoropropylene units, in which the amount of the hexafluoropropylene units is 1.0 mass% or less based on the total polymerized units, the breaking strength is 20.0 N or more, and the thermal instability index is less than 40.
[0009] The present disclosure (2) is the modified polytetrafluoroethylene according to the present disclosure (1), which has a strength ratio expressed as breaking strength (N) / extrusion pressure (MPa) of 1.80 N / MPa or more.
[0010] The present disclosure (3) is the modified polytetrafluoroethylene according to the present disclosure (1) or (2), which has a stress relaxation time of 500 seconds or longer.
[0011] The present disclosure (4) is a modified polytetrafluoroethylene in any combination with any of the present disclosures (1) to (3) having an extrusion pressure of less than 17.0 MPa.
[0012] The present disclosure (5) is a modified polytetrafluoroethylene in any combination with any of the present disclosures (1) to (4) having an extrusion pressure of less than 16.0 MPa.
[0013] The present disclosure (6) is a modified polytetrafluoroethylene containing tetrafluoroethylene units and hexafluoropropylene units, in which the amount of the hexafluoropropylene units is less than 0.1 mass% based on the total polymerized units.
[0014] The present disclosure (7) is a modified polytetrafluoroethylene in any combination with any of the present disclosures (1) to (6) in powder form.
[0015] The present disclosure (8) is a modified polytetrafluoroethylene in any combination with any of the present disclosures (1) to (7) which are fine powders.
[0016] The present disclosure (9) is an expanded body formed from modified polytetrafluoroethylene in any combination with any of the present disclosures (1) to (8). Effect of the Invention
[0017] According to the present disclosure, it is possible to provide a modified polytetrafluoroethylene that has high breaking strength but low extrusion pressure, and an extruded body using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Generally, the breaking strength of polytetrafluoroethylene (PTFE) can be increased by increasing the extrusion pressure, but the paste extrudate tends to become hard and the moldability of the extrudate tends to deteriorate. However, after extensive investigation, it was discovered that in modified PTFE using hexafluoropropylene as the modified monomer, by adjusting the composition of tetrafluoroethylene and hexafluoropropylene during polymerization within a specific range, it is possible to obtain PTFE that has high breaking strength but low extrusion pressure, contrary to common technical knowledge.
[0019] The present disclosure will now be described in detail.
[0020] The present disclosure provides a modified PTFE (hereinafter also referred to as a first modified PTFE) that contains tetrafluoroethylene (TFE) units and hexafluoropropylene (HFP) units, the amount of the HFP units being 1.0 mass% or less based on the total polymerized units, has a breaking strength of 20.0 N or more, and a thermal instability index of less than 40. The first modified PTFE has the above-mentioned constitution, and therefore, although it has high breaking strength, it has low extrusion pressure and excellent moldability. The reason for this is not clear, but it is presumed that the presence of HFP in the reaction system until the end of polymerization due to the low reactivity of HFP with TFE affects the physical properties of the resulting modified PTFE. The first modified PTFE also has excellent heat resistance.
[0021] The first modified PTFE contains TFE units (polymerized units based on TFE) and HFP units (polymerized units based on HFP), and the amount of the HFP units is 1.0 mass % or less based on the total polymerized units. The content of TFE units in the modified PTFE may be 99.0% by mass or more.
[0022] The modified PTFE may further contain polymerized units based on a modifying monomer other than TFE and HFP (other modifying monomer units).
[0023] The other modified monomer is not particularly limited as long as it is copolymerizable with TFE, and examples thereof include hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene, perfluoroolefins, perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylene, etc. The other modified monomers used may be one type or multiple types.
[0024] The content of the other modified monomer units is preferably less than 1.0% by mass, and more preferably 0.1% by mass or less, based on the total polymerized units. The total amount of the HFP units and the other modified monomer units is preferably 1.0% by mass or less based on the total polymerized units.
[0025] The content of the HFP units is 1.0% by mass or less based on the total polymerized units, but in terms of lowering the extrusion pressure and increasing the breaking strength, it is preferably 0.50% by mass or less based on the total polymerized units, more preferably 0.30% by mass or less, even more preferably 0.10% by mass or less, even more preferably 0.05% by mass or less, especially preferably 0.02% by mass or less, and particularly preferably 0.01% by mass or less. The content of the HFP units may be 0.0001% by mass or more, or may be 0.001% by mass or more, based on the total polymerized units. In this specification, the HFP unit means a part of the molecular structure of the modified PTFE that is derived from HFP.
[0026] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.
[0027] The first modified PTFE has a breaking strength of 20.0 N or more. The breaking strength is preferably 25.0 N or more, more preferably 28.0 N or more, and even more preferably 30.0 N or more. The higher the breaking strength, the better, but it may be 100.0 N or less, 80.0 N or less, or 50.0 N or less. The breaking strength is a value determined by the following method. The stretched bead (produced by stretching the bead) obtained in the stretching test carried out at a stretch speed of 100% / sec described below is clamped and fixed in a movable jaw having a gauge length of 5.0 cm, and a tensile test is carried out at 25°C and a speed of 300 mm / min, and the strength at the time of break is measured as the breaking strength.
[0028] The first modified PTFE has a thermal instability index (TII) of less than 40. In terms of lowering the extrusion pressure, increasing the breaking strength, and further improving the heat resistance, the thermal instability index is preferably 15 or less, more preferably 10 or less, and particularly preferably less than 5. The thermal instability index is also preferably −10 or more, and more preferably 0 or more. The heat instability index is measured in accordance with ASTM D 4895.
[0029] The first modified PTFE is preferably extruded at a pressure of 20.0 MPa or less, more preferably less than 18.0 MPa, even more preferably less than 17.0 MPa, and even more preferably less than 16.0 MPa. The extrusion pressure may be 5.0 MPa or more, or 10.0 MPa or more. The above extrusion pressure is a value determined by the following method. 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon Corp.) is added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. The obtained PTFE fine powder mixture is then left at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded at room temperature through an orifice (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at a reduction ratio of 100:1 (ratio of cross-sectional area of the inlet and outlet of the die) to obtain a uniform bead (beading; extrusion molded body). The extrusion speed, i.e., the ram speed, is 20 inches / min (51 cm / min). The extrusion pressure is the value obtained by measuring the load when the extrusion load reaches equilibrium in the paste extrusion and dividing it by the cross-sectional area of the cylinder used for the paste extrusion.
[0030] The strength ratio of the first modified PTFE, expressed as breaking strength (N) / extrusion pressure (MPa), is preferably 1.80 N / MPa or more, more preferably 1.85 N / MPa or more, even more preferably 1.90 N / MPa or more, even more preferably 1.95 N / MPa or more, and even more preferably 2.00 N / MPa or more. The higher the strength ratio, the better, but it may be 5.00 N / MPa or less, 4.00 N / MPa or less, or 3.00 N / MPa or less. A higher strength ratio means a higher breaking strength and a lower extrusion pressure. The breaking strength and extrusion pressure are values determined by the above-mentioned method.
[0031] The first modified PTFE is preferably stretchable. In this specification, "stretchable" is determined according to the following criteria. The bead obtained by the above paste extrusion is heated at 230°C for 30 minutes to remove the lubricant from the bead. The bead (extrudate) is then cut to the appropriate length, clamped at each end with a clamp distance of 2.0 inches (51 mm) between the clamps, and heated to 300°C in an air circulating oven. The clamps are then moved apart at a desired speed (stretch rate) until a separation distance corresponding to the desired stretch (total stretch) is achieved, and a stretch test is performed. The stretching method essentially follows that disclosed in U.S. Pat. No. 4,576,869, except for the extrusion speed (51 cm / min instead of 84 cm / min). "Stretch" is the increase in length due to stretching, and is usually expressed in relation to the original length. In the above preparation method, the stretch rate is 1000% / sec and the total stretch is 2400%. A stretchable material is considered to be stretchable if it does not break before the stretch is completed.
[0032] In the above-mentioned production method, the modified PTFE of the present disclosure is preferably subjected to a stretch test under conditions of a stretch rate of 100% / sec and a total stretch of 2400%, and does not break before the above-mentioned stretching is completed.
[0033] In order to further improve heat resistance, the first modified PTFE preferably has a stress relaxation time of 500 seconds or more, more preferably 550 seconds or more, even more preferably 600 seconds or more, and particularly preferably 650 seconds or more. The longer the stress relaxation time, the better, but it may be 2000 seconds or less, or may be 1000 seconds or less. The above stress relaxation time is a value determined by the following method. Both ends of the stretched bead obtained in the same manner as in the above stretch evaluation test, which was performed at a stretch rate of 1000% / sec, except that the clamp distance was 1.5 inches (38 mm), and a taut bead sample with a total length of 8 inches (20 cm) was obtained by connecting the bead to a fixture. The oven was maintained at 390°C and the fixture was inserted into the oven through a (covered) slit in the side of the oven. The time it took for the bead sample to break from the point of insertion into the oven was measured as the stress relaxation time.
[0034] In view of excellent extensibility, the first modified PTFE preferably has a standard specific gravity (SSG) of 2.200 or less, more preferably 2.180 or less, even more preferably 2.170 or less, even more preferably 2.160 or less, especially preferably 2.155 or less, and particularly preferably 2.150 or less. The standard specific gravity is also preferably 2.130 or more. The standard specific gravity is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895.
[0035] The first modified PTFE generally has non-melt secondary processability. The non-melt secondary processability means that the melt flow rate cannot be measured at a temperature higher than the melting point according to ASTM D-1238 and D-2116, in other words, the PTFE does not flow easily even in the melting temperature range.
[0036] The first modified PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-B-64-8022 may be used.
[0037] The first modified PTFE can be produced, for example, by a production method including a step of emulsion polymerizing TFE and HFP (and other modifying monomers as necessary).
[0038] The above emulsion polymerization can be carried out, for example, in an aqueous medium in the presence of an anionic fluorine-containing surfactant and a polymerization initiator.
[0039] The emulsion polymerization can be carried out by charging an aqueous medium, the anionic fluorine-containing surfactant, monomers and other additives as necessary into a polymerization reactor, stirring the contents of the reactor, and maintaining the reactor at a predetermined polymerization temperature, and then adding a predetermined amount of polymerization initiator to initiate the polymerization reaction. After the polymerization reaction has started, monomers, polymerization initiators, chain transfer agents, the surfactants and the like may be additionally added depending on the purpose. The surfactant may be added after the polymerization reaction has started.
[0040] The polymerization initiator is not particularly limited as long as it can generate radicals within the polymerization temperature range, and known oil-soluble and / or water-soluble polymerization initiators can be used. Furthermore, it can also be combined with a reducing agent or the like to initiate polymerization as a redox. The concentration of the polymerization initiator is appropriately determined depending on the type of monomer, the molecular weight of the desired modified PTFE, and the reaction rate.
[0041] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical polymerization initiator can be used.
[0042] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, for example, dialkyl peroxycarbonates such as diisopropyl peroxydicarbonate and disec-butyl peroxydicarbonate, peroxyesters such as t-butyl peroxyisobutyrate and t-butyl peroxypivalate, dialkyl peroxides such as di-t-butyl peroxide, and the like. In addition, di(ω-hydro-dodecafluoroheptanoyl) peroxide, di(ω-hydro-tetradecafluoroheptanoyl) peroxide, di(ω-hydro-hexadecafluorononanoyl) peroxide, di(perfluorobutyryl) peroxide, di(perfluorovaleryl) peroxide, di(perfluorohexanoyl) peroxide, di(perfluoroheptanoyl) peroxide, di(perfluorooctanoyl) peroxide, di(perfluorononanoyl) peroxide, di(ω-chloro Representative examples include di[perfluoro(or fluorochloro)acyl]peroxides such as di(ω-hexafluorobutyryl) peroxide, di(ω-chloro-decafluorohexanoyl) peroxide, di(ω-chloro-tetradecafluorooctanoyl) peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexadecafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydrododecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutanoyl) peroxide, di(trichlorooctafluorohexanoyl) peroxide, di(tetrachloroundecafluorooctanoyl) peroxide, di(pentachlorotetradecafluorodecanoyl) peroxide, and di(undecachlorodotriacontafluorodocosanoyl) peroxide.
[0043] The water-soluble radical polymerization initiator may be a known water-soluble peroxide, such as ammonium salts, potassium salts, or sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, or percarbonic acid, t-butyl permaleate, or t-butyl hydroperoxide, etc. A reducing agent such as sulfites or sulfites may also be contained, and the amount used may be 0.1 to 20 times that of the peroxide.
[0044] The amount of the water-soluble radical polymerization initiator to be added is not particularly limited, but may be added all at once, stepwise, or continuously in an amount (e.g., several ppm relative to water concentration) at least to the extent that the polymerization rate does not decrease significantly. The upper limit is a range in which the reaction temperature may be increased while removing heat from the equipment side by the polymerization reaction heat, and a more preferable upper limit is a range in which the polymerization reaction heat can be removed from the equipment side. In terms of easily obtaining the above-mentioned physical properties, particularly excellent stretching properties, the amount of the polymerization initiator added is preferably an amount equivalent to 0.1 ppm or more, more preferably an amount equivalent to 1.0 ppm or more, and is preferably an amount equivalent to 100 ppm or less, more preferably an amount equivalent to 10 ppm or less, relative to the aqueous medium.
[0045] For example, when polymerization is carried out at a low temperature of 30° C. or less, it is preferable to use a redox initiator that combines an oxidizing agent and a reducing agent as the polymerization initiator. Examples of the oxidizing agent include persulfates, organic peroxides, potassium permanganate, manganese triacetate, cerium ammonium nitrate, and bromates. Examples of the reducing agent include sulfites, bisulfites, bromates, diimines, and oxalic acid. Examples of the persulfates include ammonium persulfate and potassium persulfate. Examples of the sulfites include sodium sulfite and ammonium sulfite. In order to increase the decomposition rate of the initiator, it is also preferable to add a copper salt or an iron salt to the combination of the redox initiator. Examples of the copper salt include copper(II) sulfate, and examples of the iron salt include iron(II) sulfate.
[0046] As the redox initiator, it is preferred that the oxidizing agent is permanganic acid or a salt thereof, a persulfate, manganese triacetate, a cerium (IV) salt, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof, or a diimine. More preferably, the oxidizing agent is permanganic acid or a salt thereof, a persulfate, or bromic acid or a salt thereof, and the reducing agent is a dicarboxylic acid or a salt thereof.
[0047] Examples of the redox initiator include combinations of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, manganese triacetate / oxalic acid, manganese triacetate / ammonium oxalate, cerium ammonium nitrate / oxalic acid, and cerium ammonium nitrate / ammonium oxalate. When a redox initiator is used, either the oxidizing agent or the reducing agent may be charged in advance in a polymerization tank, and then the other may be added continuously or intermittently to initiate polymerization. For example, when potassium permanganate / ammonium oxalate is used, it is preferable to charge ammonium oxalate in a polymerization tank and continuously add potassium permanganate thereto. In this specification, when the redox initiator is described as "potassium permanganate / ammonium oxalate," it means a combination of potassium permanganate and ammonium oxalate. The same applies to other compounds.
[0048] The redox initiator is particularly preferably a combination of an oxidizing agent that is a salt and a reducing agent that is a salt. For example, the oxidizing agent which is the salt is more preferably at least one selected from the group consisting of persulfates, permanganates, cerium (IV) salts, and bromates, further preferably permanganates, and particularly preferably potassium permanganate. The reducing agent which is the salt is more preferably at least one selected from the group consisting of oxalates, malonates, succinates, glutarates and bromates, further preferably oxalates, and particularly preferably ammonium oxalate.
[0049] Specifically, the redox initiator is preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, manganese triacetate / ammonium oxalate, and cerium ammonium nitrate / ammonium oxalate, more preferably at least one selected from the group consisting of potassium permanganate / oxalic acid, potassium permanganate / ammonium oxalate, potassium bromate / ammonium sulfite, and cerium ammonium nitrate / ammonium oxalate, and even more preferably potassium permanganate / oxalic acid.
[0050] When a redox initiator is used, the oxidizing agent and the reducing agent may be added all at once at the beginning of the polymerization, the reducing agent may be added all at once at the beginning of the polymerization and the oxidizing agent may be added continuously, the oxidizing agent may be added all at once at the beginning of the polymerization and the reducing agent may be added continuously, or both the oxidizing agent and the reducing agent may be added continuously. When one of the above redox polymerization initiators is added at the beginning of the polymerization and the other is added continuously, it is preferable to gradually reduce the rate of addition in order to obtain PTFE with a low SSG, and it is further preferable to stop the addition midway through the polymerization, and the timing for stopping the addition is preferably before 20 to 40 mass % of the total TFE consumed in the polymerization reaction is consumed.
[0051] When a redox initiator is used as a polymerization initiator, the amount of the oxidizing agent added to the aqueous medium is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, even more preferably 5 ppm or more, even more preferably 10 ppm or more, and preferably 10000 ppm or less, more preferably 1000 ppm or less. The amount of the reducing agent added is preferably 0.1 ppm or more, more preferably 1.0 ppm or more, even more preferably 5 ppm or more, even more preferably 10 ppm or more, and preferably 10000 ppm or less, more preferably 1000 ppm or less. When a redox initiator is used in the emulsion polymerization, the polymerization temperature is preferably 100° C. or lower, more preferably 95° C. or lower, and even more preferably 90° C. or lower. The polymerization temperature is preferably 10° C. or higher, more preferably 20° C. or higher, and even more preferably 30° C. or higher.
[0052] As the polymerization initiator, a water-soluble radical polymerization initiator and a redox initiator are preferred in that the above-mentioned properties can be easily obtained.
[0053] The aqueous medium is a reaction medium for polymerization, and refers to a liquid containing water. The aqueous medium is not particularly limited as long as it contains water, and may contain water and, for example, a fluorine-free organic solvent such as an alcohol, ether, or ketone, and / or a fluorine-containing organic solvent having a boiling point of 40° C. or less.
[0054] In the above emulsion polymerization, a nucleating agent, a chain transfer agent, a buffering agent, a pH adjusting agent, a stabilizing aid, a dispersion stabilizer, a radical scavenger, a decomposing agent for the polymerization initiator, and the like may be used, if necessary.
[0055] The emulsion polymerization is preferably carried out with the addition of a nucleating agent, in that the above-mentioned physical properties can be easily obtained. The nucleating agent is preferably added before the start of the polymerization reaction. As the nucleating agent, a known agent can be used. For example, it is preferable that the nucleating agent is at least one selected from the group consisting of fluoropolyethers, nonionic surfactants, and chain transfer agents, and it is more preferable that the nucleating agent is a nonionic surfactant.
[0056] The fluoropolyether may, for example, be a perfluoropolyether (PFPE) acid or a salt thereof. The perfluoropolyether (PFPE) acid or salt thereof may have any chain structure in which oxygen atoms in the backbone of the molecule are separated by saturated fluorocarbon groups having 1 to 3 carbon atoms. Also, two or more types of fluorocarbon groups may be present in the molecule. A representative structure has a repeating unit represented by the following formula: (-CFCF3-CF2-O-) n (-CF2-CF2-CF2-O-) n (-CF2-CF2-O-) n -(-CF2-O-) m (-CF2-CFCF3-O-) n -(-CF2-O-) m
[0057] These structures are described by Kasai in J. Appl. Polymer Sci. 57, 797 (1995). As disclosed therein, the PFPE acid or its salt may have a carboxylic acid group or its salt at one or both ends. The PFPE acid or its salt may also have a sulfonic acid, phosphonic acid group or their salt at one or both ends. The PFPE acid or its salt may also have a different group at each end. For monofunctional PFPEs, the other end of the molecule is usually perfluorinated, but may contain hydrogen or chlorine atoms. The PFPE acid or its salt has at least two ether oxygens, preferably at least four ether oxygens, and even more preferably at least six ether oxygens. Preferably, at least one of the fluorocarbon groups separating the ether oxygens, more preferably at least two of such fluorocarbon groups, has two or three carbon atoms. Even more preferably, at least 50% of the fluorocarbon groups separating the ether oxygens have 2 or 3 carbon atoms. Also preferably, the PFPE acid or salt thereof has a total of at least 15 carbon atoms, for example, the preferred minimum value of n or n+m in the repeating unit structure above is at least 5. Two or more of the PFPE acids or salts thereof having an acid group at one or both termini may be used in the manufacturing method of the present disclosure. The PFPE acid or salt thereof preferably has a number average molecular weight of less than 6000 g / mol.
[0058] The emulsion polymerization is preferably carried out by adding a radical scavenger or a decomposer of the polymerization initiator, since it is possible to further increase the molecular weight of the modified PTFE and improve the stretchability. The radical scavenger or the decomposer of the polymerization initiator is preferably added after the start of the polymerization reaction, preferably before 10% by mass or more, preferably 20% by mass or more of the total TFE consumed in the polymerization reaction is polymerized, and preferably before 50% by mass or less, preferably 40% by mass or less is polymerized. When depressurization and repressurization are performed as described below, it is preferable to add it after that.
[0059] The radical scavenger is a compound that does not have the ability to restart after addition or chain transfer to the free radical in the polymerization system. Specifically, a compound that easily undergoes a chain transfer reaction with a primary radical or a growing radical, and then generates a stable radical that does not react with a monomer, or a compound that easily undergoes an addition reaction with a primary radical or a growing radical, and generates a stable radical, is used. Generally, the activity of what is called a chain transfer agent is characterized by the chain transfer constant and the reinitiation efficiency, but among chain transfer agents, those with a reinitiation efficiency of almost 0% are called radical scavengers. The radical scavenger can be, for example, a compound whose chain transfer constant with TFE at the polymerization temperature is greater than the polymerization rate constant and whose reinitiation efficiency is substantially zero percent. "Reinitiation efficiency is substantially zero percent" means that the generated radicals turn the radical scavenger into stable radicals. Preferably, the compound has a chain transfer constant (Cs) with TFE at the polymerization temperature (=chain transfer rate constant (kc) / polymerization rate constant (kp)) of more than 0.1. The above compound has a chain transfer constant (Cs) of more preferably 0.5 or more, even more preferably 1.0 or more, even more preferably 5.0 or more, and particularly preferably 10 or more.
[0060] The radical scavenger is preferably at least one selected from the group consisting of, for example, aromatic hydroxy compounds, aromatic amines, N,N-diethylhydroxylamine, quinone compounds, terpenes, thiocyanates, and cupric chloride (CuCl2). Examples of the aromatic hydroxy compound include unsubstituted phenol, polyhydric phenol, salicylic acid, m- or p-salicylic acid, gallic acid, and naphthol. The unsubstituted phenols include o-, m-, or p-nitrophenol, o-, m-, or p-aminophenol, p-nitrosophenol, etc. The polyhydric phenols include catechol, resorcinol, hydroquinone, pyrogallol, phloroglucinol, naphthresorcinol, etc. Examples of aromatic amines include o-, m- or p-phenylenediamine, benzidine, and the like. Examples of the quinone compound include o-, m- or p-benzoquinone, 1,4-naphthoquinone, alizarin, and the like. Examples of thiocyanates include ammonium thiocyanate (NH4SCN), potassium thiocyanate (KSCN), and sodium thiocyanate (NaSCN). Of the above radical scavengers, aromatic hydroxy compounds are preferred, unsubstituted phenols or polyhydric phenols are more preferred, and hydroquinone is even more preferred.
[0061] The amount of the radical scavenger added is preferably an amount equivalent to 3 to 500% (molar basis) of the polymerization initiator concentration from the viewpoint of reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).
[0062] The decomposer for the polymerization initiator may be any compound capable of decomposing the polymerization initiator used, and is preferably at least one selected from the group consisting of sulfites, bisulfites, bromates, diimines, diimine salts, oxalic acid, oxalates, copper salts, and iron salts. Examples of sulfites include sodium sulfite and ammonium sulfite. Examples of copper salts include copper(II) sulfate, and examples of iron salts include iron(II) sulfate. The amount of the decomposition agent added is preferably an amount equivalent to 3 to 500% (molar basis) of the initiator concentration from the viewpoint of reducing the standard specific gravity. A more preferred lower limit is 10% (molar basis), and even more preferred is 15% (molar basis). A more preferred upper limit is 400% (molar basis), and even more preferred is 300% (molar basis).
[0063] In the above emulsion polymerization, the polymerization temperature and polymerization pressure are appropriately determined depending on the type of monomer used, the molecular weight of the desired modified PTFE, and the reaction rate. Usually, the polymerization temperature is 5 to 150°C, preferably 10°C or higher, more preferably 30°C or higher, and even more preferably 50°C or higher. Also, it is more preferably 120°C or lower, and even more preferably 100°C or lower. The polymerization pressure is usually 0.05 to 10 MPaG. In terms of further increasing the breaking strength, the polymerization pressure is more preferably 0.3 MPaG or more, and even more preferably 0.5 MPaG or more. Also, the polymerization pressure is more preferably 5.0 MPaG or less, and even more preferably 3.0 MPaG or less.
[0064] In the above emulsion polymerization, the HFP concentration in the gas in the reactor at the start of polymerization (at the time of adding the initiator) is preferably 0.01 to 3.0 mol % in order to easily obtain each of the above-mentioned physical properties. Furthermore, the HFP concentration in the gas in the reactor at the time when 40 mass % of the total TFE consumed in the polymerization reaction is polymerized is preferably greater than 0 mol % and 0.2 mol % or less. The above HFP concentration is preferably maintained until the end of the polymerization reaction. HFP may be charged all at once before the start of polymerization, or a portion may be charged before the start of polymerization and added continuously or intermittently after the start of polymerization. By allowing HFP to remain until the end of the polymerization reaction, the extrusion pressure is reduced despite the increased breaking strength of the resulting modified PTFE.
[0065] In the above emulsion polymerization, it is preferable to release the pressure before 5 to 40 mass % of the total TFE consumed in the polymerization reaction is polymerized, and then to re-increase the pressure using only TFE, in order to further improve the breaking strength. The pressure reduction is preferably carried out so that the pressure inside the reactor is 0.2 MPaG or less, more preferably 0.1 MPaG or less, and even more preferably 0.05 MPaG or less. Also, it is preferably carried out so that the pressure inside the reactor is 0.0 MPaG or more. The above pressure reduction and re-increase may be carried out several times. The pressure reduction may be carried out until the pressure is reduced using a vacuum pump.
[0066] The above-mentioned production method may include a step of coagulating the above-mentioned aqueous dispersion to obtain a wet powder of the above-mentioned modified PTFE. The above-mentioned coagulation can be carried out by a known method.
[0067] The above-mentioned manufacturing method may include a step of drying the above-mentioned wet powder. The above-mentioned drying is usually carried out by using a means such as vacuum, high frequency, or hot air while keeping the above-mentioned wet powder in a state where it is not very fluid, preferably in a state where it is left stationary. Friction between powders, especially at high temperatures, generally has an undesirable effect on fine powder-type PTFE. This is because particles made of this type of PTFE have the property of easily fibrillating even with a small shear force and losing the original stable particle structure state. The drying temperature is preferably 300° C. or less, more preferably 250° C. or less, even more preferably 230° C. or less, even more preferably 210° C. or less, even more preferably 190° C. or less, and particularly preferably 170° C. or less, from the viewpoint of reducing the extrusion pressure. From the viewpoint of improving the breaking strength, the temperature is preferably 10° C. or more, more preferably 100° C. or more, even more preferably 150° C. or more, even more preferably 170° C. or more, even more preferably 190° C. or more, and particularly preferably 210° C. or more. In order to further increase the strength ratio, it is preferable to appropriately adjust the temperature within this temperature range.
[0068] The present disclosure also provides a modified PTFE (hereinafter also referred to as a second modified PTFE) which contains TFE units and HFP units, and in which the amount of the HFP units is less than 0.1 mass % based on the total polymerized units.
[0069] The content of HFP units in the second modified PTFE is less than 0.1% by mass based on the total polymerized units, but is preferably 0.05% by mass or less, more preferably 0.02% by mass or less, and even more preferably 0.01% by mass or less. The content of the HFP units may be 0.0001% by mass or more, or may be 0.001% by mass or more, based on the total polymerized units.
[0070] The content of TFE units in the second modified PTFE may be 99.0% by mass or more.
[0071] The second modified PTFE may further contain polymerized units based on a modifying monomer other than TFE and HFP (other modifying monomer units).
[0072] The other modifying monomer is not particularly limited as long as it is copolymerizable with TFE, and examples thereof include hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF]; perhaloolefins such as chlorotrifluoroethylene; perfluoroolefins; perfluorovinyl ethers; perfluoroallyl ethers; (perfluoroalkyl)ethylenes, ethylene, and the like.
[0073] The content of the other modified monomer units is preferably less than 0.1% by mass based on the total polymerized units. The total amount of the HFP units and the other modified monomer units is preferably less than 0.1% by mass based on the total polymerized units.
[0074] The second modified PTFE preferably has a breaking strength of 20.0 N or more, more preferably 25.0 N or more, even more preferably 28.0 N or more, and even more preferably 30.0 N or more. The higher the breaking strength, the better, but it may be 100.0 N or less, 80.0 N or less, or 50.0 N or less.
[0075] The second modified PTFE preferably has a thermal instability index (TII) of less than 40, more preferably 15 or less, even more preferably 10 or less, and particularly preferably less than 5. The thermal instability index is also preferably −10 or more, and more preferably 0 or more.
[0076] The second modified PTFE is preferably extruded at a pressure of 20.0 MPa or less, more preferably less than 18.0 MPa, even more preferably less than 17.0 MPa, and even more preferably less than 16.0 MPa. The extrusion pressure may be 5.0 MPa or more, or 10.0 MPa or more.
[0077] The second modified PTFE has a strength ratio expressed by breaking strength (N) / extrusion pressure (MPa) of preferably 1.80 N / MPa or more, more preferably 1.85 N / MPa or more, even more preferably 1.90 N / MPa or more, even more preferably 1.95 N / MPa or more, and even more preferably 2.00 N / MPa or more. The higher the strength ratio, the better, but it may be 5.00 N / MPa or less, 4.00 N / MPa or less, or 3.00 N / MPa or less.
[0078] The second modified PTFE is preferably expandable.
[0079] The second modified PTFE preferably has a stress relaxation time of 450 seconds or more, more preferably 500 seconds or more, further preferably 550 seconds or more, and particularly preferably 600 seconds or more. The longer the stress relaxation time, the better, but it may be 2000 seconds or less, or may be 1000 seconds or less.
[0080] The second modified PTFE preferably has a standard specific gravity (SSG) of 2.200 or less, more preferably 2.180 or less, even more preferably 2.170 or less, even more preferably 2.160 or less, especially preferably 2.155 or less, and particularly preferably 2.150 or less. The standard specific gravity is also preferably 2.130 or more.
[0081] The second modified PTFE may have similar physical properties to the first modified PTFE.
[0082] The second modified PTFE can be suitably produced by the production method explained for the first modified PTFE.
[0083] The first and second modified PTFEs are preferably in the form of a powder, and more preferably in the form of a fine powder.
[0084] The first and second modified PTFEs may be provided in the form of an aqueous dispersion. An aqueous dispersion containing particles of either the first or second modified PTFE is also a preferred embodiment of the present disclosure.
[0085] The first and second modified PTFEs preferably have an average primary particle size of 500 nm or less, more preferably 350 nm or less, even more preferably 300 nm or less, and particularly preferably 280 nm or less, and preferably 100 nm or more, more preferably 150 nm or more, even more preferably 170 nm or more, and particularly preferably 200 nm or more. The average primary particle size is measured by the following method. The modified PTFE aqueous dispersion is diluted with water until the solid content is 0.15% by mass, and the transmittance of the 550 nm projected light per unit length of the diluted latex obtained and the number-based length average particle diameter determined by measuring a specific direction using a transmission electron microscope photograph are measured to create a calibration curve. Using this calibration curve, the number-average particle diameter is determined from the measured transmittance of the 550 nm projected light of each sample, and is taken as the average primary particle diameter.
[0086] The first and second modified PTFEs may have an average aspect ratio of primary particles of 2.0 or less, preferably 1.8 or less, more preferably 1.7 or less, even more preferably 1.6 or less, even more preferably 1.5 or less, even more preferably 1.4 or less, especially preferably 1.3 or less, particularly preferably 1.2 or less, and most preferably 1.1 or less. The average aspect ratio may also be 1.0 or more. The above average aspect ratio is determined by observing the fluororesin powder or an aqueous fluororesin dispersion diluted to a solid content of approximately 1% by mass with a scanning electron microscope (SEM), processing the images of 200 or more particles randomly selected, and averaging the ratio of the long axis to the short axis.
[0087] The first and second modified PTFEs preferably have an average secondary particle size of 100 μm or more, more preferably 200 μm or more, and even more preferably 300 μm or more, and preferably 2000 μm or less, more preferably 1000 μm or less, even more preferably 800 μm or less, and particularly preferably 700 μm or less. The average secondary particle size is measured in accordance with JIS K 6891.
[0088] The first and second modified PTFEs are particularly useful as raw materials for extruded bodies. The present disclosure also provides extruded bodies formed from either the first or second modified PTFE.
[0089] The expanded body of the present disclosure can be obtained by expanding the first or second modified PTFE.
[0090] The above-mentioned stretched body is also preferably in the form of a film, a tube, a fiber, or a rod.
[0091] When the stretched body is a membrane (stretched membrane or porous membrane), it can be stretched by a known PTFE stretching method. Preferably, a sheet-like or rod-like paste extrudate is roll-stretched in the extrusion direction to obtain a uniaxially stretched film. Furthermore, a biaxially stretched film can also be obtained by stretching the film in the width direction using a tenter or the like. It is also preferable to carry out a semi-baking treatment before stretching.
[0092] The stretched body can be made into a porous body having a high porosity, and can be suitably used as a filter medium for various precision filters such as air filters and chemical filters, a support material for polymer electrolyte membranes, and the like. They are also useful as materials for products used in the fields of textiles, medicine, electrochemicals, sealing materials, air filtration, ventilation / internal pressure regulation, liquid filtration, and general consumer goods. Specific applications are given below as examples.
[0093] Electrochemical Field Dielectric material prepreg, EMI shielding material, heat transfer material, etc. More specifically, printed wiring board, electromagnetic shielding material, insulating heat transfer material, insulating material, etc. Sealing materials field Gaskets, packing, pump diaphragms, pump tubes, aircraft sealing materials, etc.
[0094] Air Filtration Field ULPA filters (for semiconductor manufacturing), HEPA filters (for hospitals and semiconductor manufacturing), cylindrical cartridge filters (for industrial use), bag filters (for industrial use), heat-resistant bag filters (for exhaust gas treatment), heat-resistant pleated filters (for exhaust gas treatment), SINBRAN filters (for industrial use), catalyst filters (for exhaust gas treatment), adsorbent filters (for HDD installation), adsorbent vent filters (for HDD installation), vent filters (for HDD installation and others), vacuum cleaner filters (for vacuum cleaners), general-purpose multi-layer felt material, GT cartridge filters (for GT compatible products), cooling filters (for electronic device housings), etc.
[0095] Ventilation / internal pressure regulation field Freeze-drying materials such as freeze-drying containers, automotive ventilation materials for electronic circuits and lamps, container applications such as container caps, protective ventilation applications for electronic devices including small terminals such as tablet terminals and mobile phones, medical ventilation applications, etc.
[0096] Liquid Filtration Semiconductor liquid filtration filters (for semiconductor manufacturing), hydrophilic PTFE filters (for semiconductor manufacturing), chemical filters (for chemical liquid treatment), pure water production line filters (for pure water production), backwash type liquid filtration filters (for industrial wastewater treatment), etc.
[0097] General consumer goods field Clothing, cable guides (movable wires for motorcycles), motorcycle clothing, cast liners (medical supporters), vacuum cleaner filters, bagpipes (musical instruments), cables (signal cables for guitars, etc.), strings (for stringed instruments), etc.
[0098] Textiles PTFE fiber (textile material), sewing thread (textile), weaving thread (textile), rope, etc.
[0099] Medical field Internal implants (extended products), artificial blood vessels, catheters, general surgery (tissue reinforcement materials), head and neck products (dura substitutes), oral health (tissue regenerative medicine), orthopedics (bandages), etc.
[0100] The first and second modified PTFEs can also be suitably used as various additives such as dust-proof additives, drip prevention agents, and battery binders, in coating applications, and in glass cloth impregnation processing applications.
[0101] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES
[0102] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.
[0103] Various physical properties were measured by the following methods.
[0104] Modified monomer unit content PTFE powder 19 The F-NMR measurement was performed, and the signal derived from the functional group was calculated based on the following formula. HFP content (mass%)=(50A / (50A+25B))×100 (A: integral value of the CF3 signal appearing around -65 ppm, B: integral value of the CF2 signal appearing around -120 ppm) The chemical shift value was determined by setting the peak top of the CF2 signal derived from the polymer main chain at −120 ppm.
[0105] Standard specific gravity (SSG) The measurements were made using samples formed in accordance with ASTM D 4895 and by the water displacement method in accordance with ASTM D 792.
[0106] Average primary particle size The modified PTFE aqueous dispersion was diluted with water to a solid content concentration of 0.15% by mass, and the transmittance of the 550 nm projected light relative to the unit length of the obtained diluted latex and the number-based length average particle diameter determined by measuring a specific direction using a transmission electron microscope photograph were measured to create a calibration curve. Using this calibration curve, the number-average particle diameter was determined from the measured transmittance of the 550 nm projected light of each sample, and was taken as the average primary particle diameter.
[0107] Average Aspect Ratio An aqueous dispersion of a fluororesin diluted to a solids concentration of approximately 1% by mass was observed using a scanning electron microscope (SEM), and images of more than 200 randomly selected particles were processed to determine the average ratio of their major axis to their minor axis.
[0108] Extrusion Pressure 21.7 g of lubricant (trade name: Isopar H (registered trademark), manufactured by Exxon Corp.) was added to 100 g of modified PTFE powder, and mixed at room temperature for 3 minutes to obtain a PTFE fine powder mixture. The obtained PTFE fine powder mixture was then left at room temperature (25°C) for at least 1 hour before extrusion, and then paste extruded at room temperature through an orifice (diameter 2.5 mm, land length 11 mm, introduction angle 30°) at a reduction ratio of 100:1 (ratio of cross-sectional area of the inlet and outlet of the die) to obtain a uniform bead (beading; extrusion molded body). The extrusion speed, i.e., the ram speed, was 20 inches / min (51 cm / min). The extrusion pressure was determined by measuring the load when the extrusion load reached equilibrium in the paste extrusion and dividing it by the cross-sectional area of the cylinder used for paste extrusion.
[0109] Extension test The bead obtained by the above paste extrusion was heated at 230°C for 30 minutes to remove the lubricant from the bead. The bead (extrudate) was then cut to the appropriate length, clamped at each end with a clamp distance of 2.0 inches (51 mm) between the clamps, and heated to 300°C in an air circulating oven. The clamps were then moved apart at a desired speed (stretch rate) until a separation distance corresponding to the desired stretch (total stretch) was achieved, and stretch testing was performed. The stretching method essentially follows that disclosed in U.S. Pat. No. 4,576,869, except for the extrusion speed (51 cm / min instead of 84 cm / min). "Stretch" is the increase in length due to drawing, and is usually expressed in relation to the original length. In the above preparation method, the stretch rate is 100% / sec and the total stretch is 2400%.
[0110] Breaking Strength The stretched bead (produced by stretching the bead) obtained in the above stretching test was clamped and fixed in a movable jaw having a gauge length of 5.0 cm, and a tensile test was performed at 25°C and a speed of 300 mm / min, and the strength at the time of break was measured as the breaking strength.
[0111] Thermal instability index (TII) Measured in accordance with ASTM D 4895.
[0112] Stress relaxation time Both ends of the stretched bead obtained in the same manner as in the above stretching test, except that the clamp distance was 1.5 inches (38 mm) and the stretching speed was 1000% / sec, and a taut bead sample with a total length of 8 inches (20 cm) was obtained by connecting them to a fixture. The oven was maintained at 390°C and the fixture was inserted into the oven through a (covered) slit in the side of the oven. The time it took for the bead sample to break from the point of insertion into the oven was measured as the stress relaxation time.
[0113] Synthesis Example 1 A white solid A was obtained by the method described in Synthesis Example 1 of WO 2021 / 045228.
[0114] Example 1 In a 6-liter stainless steel autoclave equipped with a stainless steel stirring blade and a temperature control jacket, 3580 g of deionized water, 100 g of paraffin wax, and 5.4 g of white solid A were charged, and the inside of the autoclave was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. After injecting 0.06 g of HFP with TFE, TFE was injected to make the system pressure 0.78 MPaG, and the system temperature was kept at 70 ° C. while stirring. Next, an aqueous solution of 15.4 mg of ammonium persulfate dissolved in 20 g of water was injected with TFE to start the polymerization reaction. As the polymerization reaction progressed, the system pressure decreased, but TFE was added to maintain the system temperature at 70 ° C. and the system pressure at 0.78 MPaG. When 430g of TFE was consumed from the start of polymerization, an aqueous solution of 18.0mg of hydroquinone dissolved in 20g of water as a radical scavenger was injected with TFE. The polymerization continued thereafter, and when the amount of TFE polymerized reached 1540g from the start of polymerization, stirring and the supply of TFE were stopped, and the gas in the system was immediately released to normal pressure, and the polymerization reaction was terminated. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average aspect ratio was 1.40. The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the PTFE was coagulated while stirring in a container, and then the mixture was filtered to separate the water, thereby obtaining a wet PTFE powder. The obtained PTFE wet powder was dried for 18 hours in a hot air circulation dryer set at 180° C. to obtain a modified PTFE fine powder. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0115] Example 2 A PTFE aqueous dispersion and a modified PTFE fine powder were obtained in the same manner as in Example 1, except that the drying temperature was changed to 160°C. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0116] Example 3 Except for changing the amount of HFP to 0.11 g, a PTFE aqueous dispersion and a modified PTFE fine powder were obtained in the same manner as in Example 1. The average aspect ratio was 1.38. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0117] Example 4 A PTFE aqueous dispersion and a modified PTFE fine powder were obtained in the same manner as in Example 3, except that the timing of adding hydroquinone was changed to the point when 310 g of TFE was consumed, and the supply of TFE was stopped when the amount of polymerization of TFE reached 1250 g. The average aspect ratio was 1.35. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0118] Example 5 Except for changing the amount of HFP to 0.50 g, a PTFE aqueous dispersion and a modified PTFE fine powder were obtained in the same manner as in Example 1. The average aspect ratio was 1.25. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0119] Example 6 A PTFE aqueous dispersion and modified PTFE fine powder were obtained in the same manner as in Example 5, except that the stirring and supply of TFE were stopped when 180 g of TFE was consumed from the start of polymerization, the gas in the reactor was slowly released until the reactor pressure reached 0.02 MPaG, TFE was supplied until the reactor pressure reached 0.78 MPaG, and stirring was started again. The average aspect ratio was 1.34. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0120] Example 7 In a 6-liter polymerization tank equipped with a stainless steel stirring blade and a temperature control jacket, 3580 g of deionized water, 180 g of paraffin wax, 5.4 g of white solid A, and 0.027 g of oxalic acid were charged, and the inside of the polymerization tank was replaced with nitrogen gas while heating to 70 ° C. to remove oxygen. After maintaining the temperature inside the tank at 70 ° C. while stirring, 1.88 g of HFP was added, and then TFE gas was introduced to set the pressure at 2.7 MPaG. While stirring the contents, an aqueous solution of potassium permanganate in which 3.4 mg of potassium permanganate was dissolved in deionized water was added as an initiator to start the polymerization reaction. The aqueous solution of potassium permanganate was continuously added at a constant rate, and TFE was continuously supplied so that the pressure inside the polymerization tank was constant at 2.7 MPaG. When the TFE consumption reached 530 g, the entire amount of deionized water in which 3.4 mg of potassium permanganate was dissolved was added. When the TFE consumption amount reached 1440 g, the stirring and the supply of TFE were stopped, and the TFE in the polymerization tank was purged to terminate the polymerization reaction. The aqueous dispersion was taken out and cooled, and then the paraffin wax was separated to obtain an aqueous PTFE dispersion. The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the PTFE was coagulated in a container while stirring, and then the water was filtered off to obtain a wet PTFE powder with an average aspect ratio of 1.28. The obtained PTFE wet powder was dried for 18 hours in a hot air circulation dryer set at 160° C. to obtain a modified PTFE fine powder. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0121] Example 8 A 6-liter polymerization tank equipped with a stainless steel stirring blade and a temperature control jacket was charged with 3550 g of deionized water, 180 g of paraffin wax, and 5.4 g of white solid A, and the inside of the polymerization tank was replaced with nitrogen gas while heating to 80 ° C. to remove oxygen. After maintaining the temperature inside the tank at 80 ° C. while stirring, 1.80 g of HFP was added, and then TFE gas was introduced to a pressure of 2.7 MPaG. Next, an aqueous solution of 7.2 mg of ammonium persulfate dissolved in 20 g of water was pressed in with TFE to start the polymerization reaction. When 180 g of TFE was consumed from the start of polymerization, the stirring and supply of TFE were stopped, and then the gas in the reactor was slowly released until the pressure of the reactor reached 0.02 MPaG, and then TFE was supplied until the pressure of the reactor reached 2.7 MPaG, and stirring was started again. When 410 g of TFE was consumed from the start of polymerization, deionized water in which 11.0 mg of hydroquinone was dissolved as a radical scavenger was continuously fed at a constant rate, and when the TFE consumption amount reached 1000 g, the entire amount of deionized water in which 11.0 mg of hydroquinone was dissolved was added. When the TFE consumption amount reached 1440 g, stirring and TFE feeding were stopped, and the TFE in the polymerization tank was purged to terminate the polymerization reaction. The aqueous dispersion was taken out and cooled, and the paraffin wax was separated to obtain an aqueous PTFE dispersion. The average aspect ratio was 1.31. The resulting PTFE aqueous dispersion was diluted to a solids concentration of 13% by mass, and the PTFE was coagulated while stirring in a container, and then the mixture was filtered to separate the water, thereby obtaining a wet PTFE powder. The obtained PTFE wet powder was dried for 18 hours in a hot air circulation dryer set at 160° C. to obtain a modified PTFE fine powder. The physical properties of the resulting modified PTFE fine powder were measured, and the results are shown in Table 1.
[0122] Comparative Example 1 A PTFE fine powder was obtained in the same manner as in Example 1, except that HFP was not added. The physical properties of the obtained PTFE fine powder were measured, and the results are shown in Table 1.
[0123] [Table 1]
Claims
1. A modified polytetrafluoroethylene containing tetrafluoroethylene units and hexafluoropropylene units, the amount of said hexafluoropropylene units being 1.0 mass% or less based on all polymerized units, the breaking strength being 20.0 N or more, and the thermal instability index being less than 40.
2. 2. The modified polytetrafluoroethylene according to claim 1, having a strength ratio expressed as breaking strength (N) / extrusion pressure (MPa) of 1.80 N / MPa or more.
3. 3. The modified polytetrafluoroethylene according to claim 1, which has a stress relaxation time of 500 seconds or more.
4. The modified polytetrafluoroethylene according to claim 1 or 2, wherein the extrusion pressure is less than 17.0 MPa.
5. The modified polytetrafluoroethylene according to claim 1 or 2, wherein the extrusion pressure is less than 16.0 MPa.
6. A modified polytetrafluoroethylene comprising tetrafluoroethylene units and hexafluoropropylene units, the amount of said hexafluoropropylene units being less than 0.1 mass% based on the total polymerized units.
7. The modified polytetrafluoroethylene according to claim 1 or 2, in the form of a powder.
8. The modified polytetrafluoroethylene according to claim 1 or 2, which is in the form of a fine powder.
9. 3. An extruded body formed from the modified polytetrafluoroethylene according to claim 1 or 2.
Citation Information
Patent Citations
Modified polytetrafluoroethylene fine powder and uniaxially oriented porous body
JP2015127411A
Aqueous polytetrafluoroethylene emulsion and process for production thereof, aqueous polytetrafluoroethylene dispersion obtained using the emulsion, polytetrafluoroethylene fine powder, and stretch-expanded body
WO2011055824A1
Polytetrafluoroethylene and stretched body
WO2020022355A1